2020
DOI: 10.1186/s13018-020-01605-w
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral intraosseous plasma rich in growth factor (PRGF-Endoret) infiltrations as a novel strategy for the treatment of degenerative lesions of endplate in lumbar pathology: description of technique and case presentation

Abstract: Background: Motivation and necessity to adopt minimally invasive therapies in the field of spinal regenerative medicine is increasing. Autologous platelet-rich plasma (PRP) therapy has recently been used as an effective technological and biological approach to tissue repair and has shown to improve multiple conditions including back pain and degenerative disc pathology. In addition, it is well established that the anatomic elements of the spinal system affected by degenerative pathology include the interverteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…Broadly, the groups show a statistically significant improvement in all areas at the end of the follow-up, especially in terms of pain and overall quality of life. These results are consistent with previous studies and highlight the minimally invasive treatment of back pain through PRP infiltrations (11)(12)(13)(14)(15)(16)20,21). It is noteworthy that the MCID was achieved in all subgroups for NRS scale, namely, an improvement equal to or greater than 2 points that corresponds to a decrease in pain of 2 points or more (31,32).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Broadly, the groups show a statistically significant improvement in all areas at the end of the follow-up, especially in terms of pain and overall quality of life. These results are consistent with previous studies and highlight the minimally invasive treatment of back pain through PRP infiltrations (11)(12)(13)(14)(15)(16)20,21). It is noteworthy that the MCID was achieved in all subgroups for NRS scale, namely, an improvement equal to or greater than 2 points that corresponds to a decrease in pain of 2 points or more (31,32).…”
Section: Discussionsupporting
confidence: 92%
“…Plasma rich in growth factors (PRGF) technology has been widely used as a minimally invasive biological approach to induce tissue repair and improve numerous clinical conditions of musculoskeletal system (19), including spinal structures (20,21). The treatment of spine pathologies with PRGF, namely protrusion and herniated intervertebral disc (IVD); spinal roots; neuritis produced by radicular compression, due to the direct compressive effect of the herniated disc; etc, provides pain attenuation, chondroprotection, and anti-inflammatory effect (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A herniated nucleus compresses the nerve root resulting in in ammation, and in ammatory factors are one of the primary causes of radiating pain in this condition. The diverse factors released by PRP promote cell survival and proliferation, downregulation of pro-in ammatory cytokines, suppression of tumor necrosis factor κB pathways and endogenous cannabinoid systems, subchondral bone homeostasis, and bone mineralization 17 . Using an animal experiment, Kamoda et al reported that PRP can reduce in ammatory calcitonin gene-related peptide levels in sensory neurons innervating the discs 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Recientemente se ha utilizado la aplicación intraósea en los pacientes que presentan edema óseo en plataformas vertebrales en niveles con disco degenerado. 49 Algunos autores describen un protocolo que incluye todos los niveles donde exista aumento de líquido sinovial en las facetas o disminución de la altura del disco. El tratamiento se realiza en facetas, foráminas, ramo medial, ligamentos supra e interespinoso y aplicación intramuscular del plasma pobre en plaquetas (PPP) en multifidus.…”
Section: Columnaunclassified